2015
DOI: 10.1016/j.cmi.2014.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of human papillomavirus in the anal canal of men: the HIM Study

Abstract: Human papillomavirus (HPV) infections are associated with development of anogenital lesions in men. There are no reports describing the distribution of non-alpha HPV types in the anal canal of a sexually diverse men group. The HIM (HPV in Men) Study is a multicenter study of the natural history of HPV infection in Brazil, Mexico and USA. At baseline, 12% of anal canal specimens PCR HPV-positive were not typed by the Roche Linear Array and were considered unclassified. Our goal was characterizing HPVs among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 27 publications
7
23
2
1
Order By: Relevance
“…Nevertheless, these results are consistent with our prior findings using a PCR-sequencing method 17 . Higher β-HPV prevalence was observed at the anal canal among middle-aged adults (31–44 years) and older men (>45 years) compared to younger men (18–30 years), whereas no age associations were observed for the external genital skin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, these results are consistent with our prior findings using a PCR-sequencing method 17 . Higher β-HPV prevalence was observed at the anal canal among middle-aged adults (31–44 years) and older men (>45 years) compared to younger men (18–30 years), whereas no age associations were observed for the external genital skin.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, these findings contrast with the 40% of β-HPV prevalence observed in male genital skin specimens using a PCR-sequencing protocol 16,32 . A similar prevalence was observed regarding β-HPV detection at the anal canal of HIM participants (54.3% by Luminex versus 31.6% with PCR-sequencing) 17 . Therefore, recently most studies take advantage of the higher sensitivity inherent of the Luminex technology for cutaneous HPV DNA detection (Gheit et al 2007; Donà et al 2015; Torres et al 2015).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Indeed, the recently reported high prevalence of β-HPVs in fingernail samples [43] supports the likelihood of fingers serving as a source of transmission of cutaneous HPVs among distant anatomical sites. Nevertheless, one may not discard that these findings might solely reflect the deposition of virions shed from other anatomic sites [20, 32]. Still, a recent study conducted among heterosexual couples examining anogenital β-HPVs concordance and transmission, suggested that these infections may, at least in part, be sexually transmitted [21].…”
Section: Epidemiology Of Beta Hpvmentioning
confidence: 99%
“…Within participants of a multinational study focused on the natural history of HPV infection in men (HIM study) [28], DNA from multiple β-HPVs were detected in the male genitals, anal canal and oral samples [29-32]. Furthermore, among these men, any β-HPVs were more prevalent in the genital skin (81.6%) compared to the forearm skin (64.4%) and EBH (60.9%) [33].…”
Section: Epidemiology Of Beta Hpvmentioning
confidence: 99%